2022
DOI: 10.1093/sleep/zsac273
|View full text |Cite
|
Sign up to set email alerts
|

Sleep architecture is associated with core symptom severity in autism spectrum disorder

Abstract: Objective While caregiver-reported sleep disturbances are common in children and adolescents with autism spectrum disorder (ASD), few studies have measured objective sleep in ASD compared to controls, and their findings are mixed. We investigated 1) differences in sleep architecture, specifically slow-wave sleep (SWS) and rapid eye movement sleep (REM), between ASD and typically developing controls (TD); and 2) if any observed differences in sleep were associated with core ASD symptoms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
1
2
1
Order By: Relevance
“…Similar to Kurz et al(41) and Mylonas et al(20) we observed a comparable distribution of sleep stages between the two groups. This is in contrast to several other studies which showed an increased SWS and decreased REM sleep ratio(40), including Buckley et al 2010 who reported on a smaller, earlier version of this dataset. By the time of our analysis the TD group size had doubled and the ASD group increased by half, which may explain these different observations.…”
contrasting
confidence: 95%
See 3 more Smart Citations
“…Similar to Kurz et al(41) and Mylonas et al(20) we observed a comparable distribution of sleep stages between the two groups. This is in contrast to several other studies which showed an increased SWS and decreased REM sleep ratio(40), including Buckley et al 2010 who reported on a smaller, earlier version of this dataset. By the time of our analysis the TD group size had doubled and the ASD group increased by half, which may explain these different observations.…”
contrasting
confidence: 95%
“…By the time of our analysis the TD group size had doubled and the ASD group increased by half, which may explain these different observations. Of note our ASD group displayed a decreased TST, similar to that inBuckley et al 2010 andKawai et al 2022.…”
supporting
confidence: 70%
See 2 more Smart Citations
“…People with autism are more likely to experience sleep issues than those in the general population, because they have a genetic mutation that affects melatonin levels, a natural hormone that regulates sleep. Only 15% of their sleep time is spent in the rapid eye movement (REM) stage of sleep, which is essential for learning and memory retention [ 23 ]. Sleep disorders also influence the brain’s production of neurotransmitters, including dopamine and serotonin (5-hydroxytryptamine, or 5-HT), as well as other irregularities.…”
Section: Introductionmentioning
confidence: 99%